ANALISIS HUKUM EKONOMI SYARIAH TERHADAP PELAKSANAAN JAMINAN ASURANSI KESEHATAN DI BPJS KESEHATAN BANDUNG - Azminur Naila Najah (Al-Muamalat: Jurnal Ekonomi Syariah, 2018)
In connection with the Decisions and Recommendations of the Ulama 'MUI Fatwa Commission in Indonesia concerning the Implementation of National Health Insurance by BPJS Health agreed to clarify the illegitimate issues that developed in the community and that the government establish rules, systems, and format the modus operandi of BPJS Health in accordance with the principles sharia. Based on these considerations it is necessary to stipulate a fatwa on the Guidelines for the Implementation of Health Social Security in accordance with Islamic Sharia to be used as a guideline. So on December 22, 2015, the National Sharia Council of the Indonesian Ulema Council decided and established the DSN-MUI Fatwa No.98 / DSN-MUI / XII / 2015 concerning Guidelines for Implementing Sharia Health Social Security. The method applied in this qualitative research is descriptive method, which is research intended to investigate the conditions, conditions or other things that have been mentioned, the results of which are presented in the form of research reports, the data of which is obtained through interviews, documentation, and literature studies. The implementation of health insurance coverage at BPJS Health Bandung both in terms of membership, registration, fees, services, and the mechanism for payment of fines is carried out properly and in accordance with the existing legislation. However, it is not in accordance with the provisions in the DSN-MUI Fatwa No.98 / DSN-MUI / XII / 2015 concerning Guidelines for Sharia Health Social Security Implementation because it has not fulfilled all the elements of its contract, does not have a Social Security Fund holding account in Islamic banks, earns income from interest, the development and placement paths of DJS are not clear and the investment is not in a place that is in accordance with sharia.